Novel cancer antigens for personalized immunotherapies: latest evidence and clinical potential - Wurz, Gregory T. (Ther Adv Med Oncol, 2016)
The clinical success of monoclonal antibody immune checkpoint modulators such as ipilimumab, which targets cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), and the recently approved agents nivolumab and pembrolizumab, which target programmed cell death receptor 1 (PD-1), has stimulated renewed enthusiasm for anticancer immunotherapy, which was heralded by Science as ‘Breakthrough of the Year’ in 2013. As the potential of cancer immunotherapy has been recognized since the 1890s when William Coley showed that bacterial products could be beneficial in cancer patients, leveraging the immune system in the treatment of cancer is certainly not a new concept; however, earlier attempts to develop effective therapeutic vaccines and antibodies against solid tumors, for example, melanoma, frequently met with failure due in part to self-tolerance and the development of an immunosuppressive tumor microenvironment. Increased knowledge of the mechanisms through which cancer evades the immune system and the identification of tumor-associated antigens (TAAs) and negative immune checkpoint regulators have led to the development of vaccines and monoclonal antibodies targeting specific tumor antigens and immune checkpoints such as CTLA-4 and PD-1. This review first discusses the established targets of currently approved cancer immunotherapies and then focuses on investigational cancer antigens and their clinical potential. Because of the highly heterogeneous nature of tumors, effective anticancer immunotherapy-based treatment regimens will likely require a personalized combination of therapeutic vaccines, antibodies and chemotherapy that fit the specific biology of a patient’s disease.